Neural adaptations to resistance training - Deng, Fu-Yu (2023)
Ageing-related alterations in neuromuscular system was the main interest in the current study. Muscle strength decrement may be one of the most evident changes. The impairment in strength through aging may lead to functional impairments, such as falling. In order to prevent functional loss, performing strength training has been reported to be one of the effective ways to preserve or even improve muscular strength. Except for the muscular system, the nervous system may contribute to strength gain as well. The current study aimed to compare the difference in corticospinal excitability and inhibition following resistance training and detraining between young and older adults.